Beneficial Root Endophytic Fungi Increase Growth and Quality Parameters of Sweet Basil in Heavy Metal Contaminated Soil - Sabra, Mayada; Aboulnasr, Amal; Franken, Philipp; Perreca, Erica; Wright, Louwrance Peter; Camehl, Iris (Frontiers in Plant Science, 2018)
How interactions between plants, the rhizosphere, and contaminated soil affect environmental sustainability is still under research. We tested the effects of two root endophytic fungi, the arbuscular mycorrhiza fungus (AMF) Rhizophagus irregularis and the beneficial endophyte Serendipita indica, on sweet basil (Ocimum basilicum) growing on soil contaminated with lead and copper in a pot experiment under defined greenhouse conditions. Both fungi caused an increase in shoot and root dry weight of sweet basil plants under all conditions and decreased the amount of lead in shoots. The amount of copper was reduced by S. indica, while the AM fungus showed this effect only when the soil is contaminated with both copper and lead. Furthermore the AMF, but not the endophyte S. indica caused a strong increase on the concentrations of the essential oils linalool and eucalyptol even on sweet basil growing on contaminated soils. Hence, cultivating sweet basil in combination with beneficial fungi in case of difficult environmental conditions could be of interest for industry located in countries with widespread land pollution, because quantity and quality of plants are increased while the amount of heavy metals is generally reduced.